Sistema de sensoriamento remoto de umidade e temperatura do solo para irrigação de precisão - Santos, Clemilson Costa dos (2008)
In the region of the northeastern semiarid, there is a great necessity of water and energy economy and the agriculture handling methods necessitate to put into effect these resources in a more accurate way. In this work the development of a remote monitoring system of humidity and ground temperature, to use in irrigated horticultures, substituting the manual harvest methods of automatic systems in real time is presented. The work integrates the technologies related to sensors, integrated circuits and cordless communication concerning the development of remote modules which have sensors of humidity, temperature, radio, battery and processing unit with autonomous operation. The remote modules were projected to be distributed inside the cultivated areas. A communication protocol between the remote modules and the master module was modeled in Colored Petri Nets (CPN) and the prototype was sat up and tested in a laboratory and in the fields, in a producer watermelon area. The tests revealed the practicality in the installation and redistribution of the modules. The module communications layout was well succeeded once that it achieved the satisfactory distances (a reach of 142 meters) with a baud rate of 38.4 kbits/s inside a cultivation area and also because it is capable to multiply its reach through the use of cooperative communication routines. The accomplished results of this project were the creation of a low cost platform (compared to the industrial solutions available in the commerce) capable of attending the researcher and be accessible to the rural producer who aims to reduce his costs with water, energy and inputs, investing in support technologies. The evolution of the works on this segment points to a future in which the remote sensors will become a tool used in a large variety of applications, adding new ways to observe the phenomena which govern nature and its relationship with men.